PENIDIDKAN KARAKTER DALAM KELUARGA - Lilis Satriah (Cendekia: Kependidikan dan Kemasyarakatan, 2011)
Character education implemented at the school recently will run well if it is supported by character education at home. It can not be denied that the percentage of the pupils’ activity learning at school is only about 10% to 15% less than that of their activities at home. As a result of this case, the implementation of character building by teachers at school is obviusly limited when it is compared with the educational policies adopted by the parents at home. To make the matter worse, it might be possible that the character education built by teachers in the classroom is able to be broken down by the parents' attitudes abusive to the pupils at home. To fill this void, therefore, the application of character education in the family is one of golden ways to anticipate the occurrence of various problems that occur in the community life. By implementing character education in the family, it means that the parents have prepared their children who have good character and morals and become heir to the cadres and leaders of the nations in the future. Thus, the essential thing to note is that how the parents realize the importance of good and proper parenting, in so doing, they will have self-awareness to suit their parenting styles that best fit to their children needs and wants, and always try to improve their insight and knowledge about parental system.لاتنجح التربية الأخلاقية التي قام بها المدرسة إلا بدعم التربية الأخلاقية التي قام بها الوالدان في البيت. لأن الطالب قضى أكثر أوقاته في البيت، ويقضي فقط 10 – 15 في المئة من أوقاته في المدرسة. وبهذا ، تطبيق التربية الأخلاقية في المدرسة أقل قدرا بالنسبة للتربية الأخلاقية التي قام بها الوالدان في الأسرة. وقد تفسد نتائج التربية الأخلاقية في المدرسة بسوء التصرفات نحوه من قبل الوالدين.  وبهذا كانت التربية الأخلاقية في الأسرة عنصرا هاما في إعداد الطالب لمواجهة المشكلات في المجتمع. وفي هذا قد أعدت الأسرة شبانا متخلقين بأخلاق كريمة الذين – في المستقبل -  سيكونون رؤساء ورجالا . الأمور التي لابد أن ينتبه إليها الآباء والأمهات هي التربية الأخلاقية في الأسرة، حيث يحاول الوالدان في تحسين أدائها والتزود بالمعارف والعلوم عن التربية الصحيحة.